Novel soluble octa-substituted phthalocyanines bearing chloro and long alkyl chain containing fluorine: Synthesis, characterization and photophysical and photochemical properties - Erdogmus, Ali; Arici, Mursel (ELSEVIER SCIENCE SA, 2014)
The synthesis of a new phthalonitrile (1), together with photophysical, photochemical and spectral properties of the resulting peripherally octakis zinc, magnesium and oxotitanium phthalocyanines (2, 3 and 4) are described for the first time. New compounds 1-4 have been synthesized and characterized by elemental analysis, IR, H-1 NMR, mass spectra and electronic spectroscopy. Complexes 2, 3 and 4 have good solubility in organic solvents such as CHCl3, DCM, THF and toluene. In this study, fluorescence quantum yield (photophysic), fluorescence behavior, singlet oxygen quantum and photodegradation quantum yields (photochemistry) and spectral properties of these new complexes were studied in THF. Aggregation was not observed in the presence of a long alkyl chain containing fluorine in the complexes. The effects of metal and the fluoro-functional groups on new peripherally octa-substituted metallophthalocyanines on the photophysicochemical parameters of the phthalocyanines (2,3 and 4) were also investigated. (C) 2014 Elsevier B.V. All rights reserved.
Keywords: Zinc; Magnesium and oxo-titanium phthalocyanines; Fluorescence quantum yield; ZINC PHTHALOCYANINES; SPECTROELECTROCHEMICAL PROPERTIES; PHOTODYNAMIC THERAPY; COMPLEXES; DERIVATIVES; POSITIONS; MANGANESE; COBALT; Chemistry